2004
DOI: 10.1002/j.1556-6978.2004.tb01843.x
|View full text |Cite
|
Sign up to set email alerts
|

Program Directors' Perceptions of Admission Screening Measures and Indicators of Student Success

Abstract: The purpose of the current research was to ascertain program directors' perceptions of the effectiveness of applicant screening measures currently used in counselor education programs accredited by the Council for Accreditation of Counseling and Related Educational Programs and their perceptions of the effectiveness of measures of graduate student success. The personal interview was identified as the most effective screening measure currently used, and practicum/internship performance was considered the most e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
(17 reference statements)
1
10
0
Order By: Relevance
“…Surveys of Council on the Accreditation of Counseling and Related Education Programs (CACREP) accredited counselor education programs have noted that the interview was highly esteemed by survey respondents as an effective screening measure for admission (Leverett-Main 2004;Smith 2004). It would appear on first blush that the interview would be a means of assessing the personal characteristics of the potential counselor trainee in ways that a focus on academic or intellectual ability alone could not accomplish.…”
Section: Cacrep Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys of Council on the Accreditation of Counseling and Related Education Programs (CACREP) accredited counselor education programs have noted that the interview was highly esteemed by survey respondents as an effective screening measure for admission (Leverett-Main 2004;Smith 2004). It would appear on first blush that the interview would be a means of assessing the personal characteristics of the potential counselor trainee in ways that a focus on academic or intellectual ability alone could not accomplish.…”
Section: Cacrep Guidelinesmentioning
confidence: 99%
“…Ideally, these decisions are a result of consistent findings regarding the inadequacy of traditional measures, such as the Graduate Records Exam (GRE) or the use of interviews, as sufficient for a thorough evaluation of applicants. Though the GRE has been consistently used as one measurement for admission to graduate counseling training (Leverett-Main 2004;Smith 2004) repeated findings have deemed the focus on measures of academic ability, the GRE in particular, to be inadequate in terms of admissions decisions for counseling students (Chernyshenko and Ones 1999;Goldberg and Alliger 1992;House and Johnson 1993;Leverett-Main 2004;Sternberg and Williams 1997).…”
mentioning
confidence: 98%
“…Personality characteristics and level of selfawareness are less easy to quantify than a test score such as the GRE. Therefore, a disadvantage to this admissions model might be the need to balance objective measures with these less quantifiable, yet qualitative measures that the literature suggest should be considered in screening potential candidates for counselor education programs (Leverett-Main, 2004;Smaby et al, 2005).…”
Section: Unsatisfactory Carkhuff Score and Satisfactory Performance Imentioning
confidence: 99%
“…The research in this area examined the relationship between the nontraditional academic factors, or the attributes of the counselor, and counselor effectiveness, and found mixed results, concluding that the relationship was ambiguous at best (Atkinson, Stasco & Hosford, 1975: Osipow & Walsh, 1973, while other studies indicated the existence of a relationship (Anthony & Wain, 1971;Hurst & Shatkin, 1974: McKee, et al, 1974Rothstein, 1988;Tinsely & Tinsely, 1977). Indeed, Leverett-Main (2004) indicated that the skill of a counselor is less dependent on academic aptitude and more on personal qualities and interpersonal skills which might be best assessed through an interview process. Furthermore, TorresRivera, Wilbur, Maddux, Smaby, Phan, & Roberts-Wilbur (2002) argue that personal awareness was essential to the appropriate use of counseling skills.…”
Section: Figure 2 the Wellness Cube Model Bottom Viewmentioning
confidence: 99%
“…As a second contribution, earlier literature on the influence of student selection has mainly used descriptive and correlational methodologies (e.g, Leverett-Main, 2004;Arnold and van den Brink, 2010;Moore, Offenstein & Shulock, 2009). Unfortunately, if a proper control group is lacking, one cannot obtain causal evidence.…”
Section: Introductionmentioning
confidence: 99%